Chemical Attributes of Soil and Forage Yield of Pasture Recovered with Phosphate Fertilization and Soil Management - Rebonatti, M. D. [UNESP]; Fabrice, C. E. [UNESP]; Santos, J. M.F. [UNESP]; Heinrichs, R. [UNESP]; Filho, C. V. Soares [UNESP]; Moreira, A. (Taylor & Francis, 2016)
Extensive and semi-extensive pastures are the basis of Brazilian livestock production. However, much of it is degraded or in degradation process, with low stocking rate per area. Even with this problem, this management type is 60% and 50% of Australia’s and the United States’ production costs, respectively. In order to research alternatives for Urochloa decumbens degraded pasture recovery in an Oxisol, Stylosanthes (Stylosanthes spp.) “Campo Grande” cultivar was introduced and phosphate fertilization was applied. The experimental design was of randomized blocks, 7 × 2 × 2 factorial design, with four replicates, involving seven systems to introduction (U. decumbens control; partial desiccation with 1.5 L ha−1 glyphosate, total desiccation with 3.0 L ha−1 glyphosate; direct planting; scarification, harrowing, and plowing + harrowing), phosphate fertilizer presence or absence, and two evaluation periods. “Campo Grande” Stylosanthes legume introduction increased shoot dry weight (SDW) yield, except in direct planting. Phosphorus fertilization increased SDW yield only in the first period, and Stylosanthes introduction in the pasture has not changed soil chemical properties. Phosphorus (P) fertilization also provided available P and exchangeable calcium (Ca2+) content in the soil increase, in addition to sum of bases and cation exchange capacity increase.
Keywords: Forage yield; soil fertility; Stylosanthes; Urochloa decumbens